Irritable bowel syndrome in China: a review on the epidemiology, diagnosis, and management. Issue 12 (20th June 2021) - Liu, Yi-Lin; Liu, Jin-Song
Abstract : Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disease worldwide. Current guidelines of IBS are mostly based on the western populations and expected to vary in different communities. China has a large population and a vast literature is available on IBS. Due to linguistic variations in the literature, the studies are not widely known and their conclusions thus remain largely obscured to the western medical literature. In this article, we reviewed the published literatures on the investigations of IBS epidemiology, diagnosis, and management in the Chinese population and emphasized the different findings gleaned from the western publications. The detailed literature review will benefit understanding of and promote future study on IBS.